1996
DOI: 10.1007/bf00018710
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of periphyton community structure and function on tile and cobble substrata in experimental stream mesocosms

Abstract: Periphyton communities are an ecologically important source of information when conducting experimental stream ecotoxicological studies . Experimental stream studies often utilize unreplicated systems in order to understand dose-response phenomena . The objective of this study was to examine the robustness of such a dose-response investigation . Autotrophic and heterotrophic periphyton were evaluated in replicated control experimental streams with open recruitment (once-through flow design) . Measurements of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…It is essential that model ecosystems are in approximately the same ecological state prior to chemical exposure . In addition to the ''selective pressure'' applied to the model by the test chemical, use of natural waters in flow-through designs carrying biota appears to result in lotic model systems being less divergent (stream-to-stream) in long-term experiments than has been observed for lentic model ecosystems (Hill et al, 1994;Rodgers et al, 1996;Lowe et al, 1996). Note.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…It is essential that model ecosystems are in approximately the same ecological state prior to chemical exposure . In addition to the ''selective pressure'' applied to the model by the test chemical, use of natural waters in flow-through designs carrying biota appears to result in lotic model systems being less divergent (stream-to-stream) in long-term experiments than has been observed for lentic model ecosystems (Hill et al, 1994;Rodgers et al, 1996;Lowe et al, 1996). Note.…”
mentioning
confidence: 90%
“…Kania et al (1976) in a long-term study of mercury exposure in large experimental channels found abundance of periphyton and invertebrates to differ on glass slides, glass dishes, ceramic, and cement substrates; however, the overall interpretation of ecological responses was the same regardless of substrate. Similarly, Lowe et al (1996) and Guckert (1996) have found that periphyton on cobble and gravel substrates responded qualitatively, and to a large degree quantitatively, the same during surfactant exposures in model ecosystems. The less uniform gravel was slightly more taxonomically diverse than the laminar surface of the tile.…”
mentioning
confidence: 92%
“…Periphytic diatoms have been extensively studied during the last 10 years, and they have been used as indicators of water system qua lity (Lecointe et al 1993, Prygiel et al 1996, Whitton & Rott 1996, Vinebrooke & Graham 1997. Some of their most interesting properties are very fast growth, high taxonomic and physiological diversity, and thenpresence in all aquatic ecosystems (Lowe et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The community grew again through Week 6 and then growth dramatically increased (over an order of magnitude) from Week 6 to 8. The density of cells on the tiles seen from Weeks 0 through 6 are what one would expect if the tile was covered with a monolayer of cells of ''standard'' bacterial size of approximately 1 × 2 m. The increases in cell density at Week 8 occurred concurrently with the development of filamentous algae observed to colonize the tiles at that time (Lowe et al, 1996).…”
Section: Bacterial Cell Densitymentioning
confidence: 93%